Early Childhood Supervision Managerial Supervision Management to Improve Managerial Competence of Playgroup Leaders: (Case Study at Calakan Playgroup in Ciburial Village, RT. 02/05 Cibogo Village, Lembang District, West Bandung Regency) - Noorfaidah, Rinrin; Kuswarno, Engkus; Mardiana, Dinny; Rostini, Deti (Journal of Islamicate Studies, 2022)
Efforts to produce quality human resources start at an early age so that development is not only physical but optimizes all existing potential. The competencies possessed by a school principal in each institution will be different, while the concept of quality assurance by the government is evaluated with the same educational standards. Managerial Supervision is an assessment activity in aspects that support the teaching and learning process related to the school management section which includes planning, organizing, implementing and supervising. In general, this study aims to analyze and find empirically about the supervision carried out by PAUD inspectors in improving the competence of the head of the Calakan Play Group in Lembang. The method used by the author in this research is descriptive analytic method with case study type. In this study, researchers used data collection techniques by means of observation, documentation, and interviews. The results of the research obtained in the planning of PAUD Supervisory Managerial Supervision has a five-year program formulation made by Intermediate Supervisors. The organization is appointed by the PAUDNI Division which consists of a chairman, secretary, PAUD supervisors and several pamong. Implementation is sometimes not according to the planned schedule/time. In supervision, PAUD supervisors have recommended suggestions to the Head of the Calakan Play Group to make a follow-up plan both for improving the managerial competence of the Head, the learning process, fulfilling the 8 National Education Standards and the quality of the Calakan Play Group itself on an ongoing basis according to the points of the Supervision Format. and Monitoring. The obstacle faced is the lack of PAUD inspectors in Lembang District. Efforts to overcome this: 1) carry out more intense communication and monitoring; 2) recommend the results of supervision to the KBB Education Office through the Section Head of PAUD and PNFI; 3) share knowledge, experience with the Supervisor at the Head of the Playing Group in terms of managing supervision and improving the competence, professionalism and experience of fellow Supervisors.